THE FINANCIAL LEASING MARKET FROM THE PERSPECTIVE OF CURRENT LEGAL REALITIES - Raluca Antoanetta Tomescu (Perspectives of Law and Public Administration, 2022)
Leasing has established itself as one of the most profitable means of financing productive investments, bringing more security to those who do not have enough capital. The benefits that leasing operations bring to the parties involved are evidenced both by the practical results that they have had over time and by the rise that leasing has had in the capital markets of the world economy. The dynamics of social development, but also the specific expansion of a market economy in a continuous process of restructuring, amid economic, social and institutional changes, require a reform of national legislation, in line with current realities and the goal of achieving a European and international economic and monetary unit. The modeling of the current legislative framework, in accordance with the requirements of society, will have as its main interest, not only to provide adequate and immediate solutions to economic and social realities, but also to eliminate legal traditions that have destabilized this market segment in recent years. For this reason, I structured my study, presenting a series of imperfections of the law that have negatively influenced the evolution of leasing in recent years.